The Effect of Academic Procrastination and Time Management on Teacher Job Stress: A Study at MA Al-Mukarrom Ponorogo - Luluk Fuadah; Wirawan Fadly; Elfi Yuliani Rochmah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2026)
Teachers are increasingly exposed to work-related stress due to growing professional demands and workload, which may adversely affect their physical and psychological well-being. This study investigates the effects of academic procrastination and time management on teachers' work stress. A quantitative approach with an ex post facto design was employed. Data were collected through observations, documentation, and questionnaires administered to 48 teachers selected using a saturated sampling technique. The research instrument was validated using Aiken’s V and tested for reliability using Cronbach’s Alpha. Data were analyzed using simple and multiple linear regression. The findings reveal that academic procrastination has no significant effect on teachers’ work stress (p = 0.897), whereas time management has a significant effect (p < 0.001). Simultaneously, academic procrastination and time management explain 44.2% of the variance in teachers’ work stress. These findings suggest that teachers are generally capable of completing academic tasks despite delaying their execution, indicating that procrastination does not necessarily increase work stress. In contrast, ineffective time management contributes substantially to elevated stress levels, particularly when teachers face heavy workloads and strict deadlines. Under certain circumstances, academic procrastination may function as a temporary coping strategy that helps teachers regulate psychological pressure arising from demanding work schedules. Therefore, improving time management skills may be a more effective strategy for reducing teachers’ work stress than focusing solely on minimizing procrastination.